2005
DOI: 10.1111/j.1572-0241.2005.50096.x
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mystery of the Gastroesophageal Junction: A Pathologist's Perspective

Abstract: The gastroesophageal junction (GEJ), which is defined as the point where the distal esophagus joins the proximal stomach (cardia), is a short anatomic area that is commonly exposed to the injurious effects of GERD and/or Helicobacter pylori infection. These disorders often lead to inflammation and intestinal metaplasia (IM) of this anatomic region. The true gastric cardia is an extremely short segment (<0.4 mm) of mucosa that is typically composed of pure mucous glands, or mixed mucous/oxyntic glands that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 85 publications
2
100
0
2
Order By: Relevance
“…The other resembles adenocarcinoma of distal esophagus and is likely to be due to the damage of short-segment gastroesophageal reflux. These two chronic damages contributes to the high incidence of IM and inflammation at the cardiac mucosa (Odze, 2005;McColl, 2006). Our previous research showed that the incidence of IM in tissue adjacent to gastric cardiac adenocarcinoma is much higher than gastric cardiac biopsy tissue from normal population (Gao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The other resembles adenocarcinoma of distal esophagus and is likely to be due to the damage of short-segment gastroesophageal reflux. These two chronic damages contributes to the high incidence of IM and inflammation at the cardiac mucosa (Odze, 2005;McColl, 2006). Our previous research showed that the incidence of IM in tissue adjacent to gastric cardiac adenocarcinoma is much higher than gastric cardiac biopsy tissue from normal population (Gao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, the first gland may be connected to the observation of various extents of so-called cardia mucosa, which is characterized by an absence of parietal cells and chief cells adjacent to the gastroesophageal junction. 8,50 Recent studies have implicated the first gland as the source of reparative metaplasia in the setting of Barrett's epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous investigations have noted the presence of glands lacking parietal cells at the squamocolumnar junction in the mouse stomach. 10 Although other studies have noted the presence of large concentrations of tuft cells in the first gland of the rodent stomach distal to the limiting ridge, 2 few investigations have defined the characteristics of the other lineages that reside at this important transition point.…”
Section: Research-article2016mentioning
confidence: 99%
“…2). The stratum granulosum is the most luminal layer and provides a permeability barrier [17,18,19,20]. This permeability barrier is composed of cell membranes in combination with junctional complexes that prevent direct diffusion of luminal contents into the cells or the intercellular spaces.…”
Section: Second Line Of Defense - the Multilayered Squamous Epitheliummentioning
confidence: 99%